Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 3875 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Dendroica fusca (Statius Müller, 1776)", { "or" : [ "Country is Panama", "Country is Nicaragua", "Country is Colombia", "Country is Ecuador", "Country is Venezuela (Bolivarian Republic of)" ] } ] } The dataset includes 3875 records from 45 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003417-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences